Korean Brinkmanship, American Provocation, and the Road to War: The Manufacturing of a Crisis - Tim Beal (Japan Focus)
The exchange of artillery fire between South and North Korea on 23 November, 2010 had predictable results - a great increase of tension on the peninsula, a show of force by the United States, and a torrent of uninformed media articles and pontificating from the security industry.Tim Beal probes the historical background to the recent incident that has brought the two Koreas, as well as the United States and China, to the brink of a new Korean War, and what can be done to address the issues.